Microbiological interactions with cold plasma - Bourke, P.; Ziuzina, D.; Han, L.; Cullen, P.J.; Gilmore, B.F. (Journal of applied microbiology, 2017)
Summary There is a diverse range of microbiological challenges facing the food, healthcare and clinical sectors. The increasing and pervasive resistance to broad‐spectrum antibiotics and health‐related concerns with many biocidal agents drives research for novel and complementary antimicrobial approaches. Biofilms display increased mechanical and antimicrobial stability and are the subject of extensive research. Cold plasmas (CP) have rapidly evolved as a technology for microbial decontamination, wound healing and cancer treatment, owing to the chemical and bio‐active radicals generated known collectively as reactive oxygen and nitrogen species. This review outlines the basics of CP technology and discusses the interactions with a range of microbiological targets. Advances in mechanistic insights are presented and applications to food and clinical issues are discussed. The possibility of tailoring CP to control specific microbiological challenges is apparent. This review focuses on microbiological issues in relation to food‐ and healthcare‐associated human infections, the role of CP in their elimination and the current status of plasma mechanisms of action.